Lithium-rich positive electrode material and preparation method and application thereof

Through co-deposition method and ALD process, the introduction of Mo atoms and doping system is formed in Li[Ni-Co-Mn]O2 positive electrode material, which solves the problems of material circulation performance and thermodynamic stability, and improves the electrochemical performance of lithium-ion batteries and Multiplying capability.

CN119240807AActive Publication Date: 2025-01-03湖南泓原新能源科技有限公司
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411766876.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-01-03
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

Li[Ni-Co-Mn]O2 ternary cathode material has shortcomings in cycling performance, thermodynamic stability and electrochemical properties, especially under high charging cutoff voltage and high magnification, and the material is prone to cationic mixed discharge and Side reactions lead to a decrease in electrochemical performance.

Method used

The lithium-rich cathode material was prepared by co-deposition method. Mo atoms were deposited using the ALD process on the WO3 substrate, and polyethylene glycol, alkyl quaternary ammonium base and cellulose were added to the intermediate liquid to form a doping system and a cladding layer. , regulate lithium content and element ratio, and improve the structural stability and electrochemical properties of the material.

Benefits of technology

It significantly improves the rate performance and cycling performance of the positive electrode material, reduces charge transfer resistance, enhances the oxygen vacancy effect, ensures the return of lithium ions, and improves the electrochemical performance and capacity retention rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119240807A_ABST
    Figure CN119240807A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of positive electrode materials, and particularly discloses a lithium-rich positive electrode material and a preparation method and application thereof. The invention relates to a preparation method of a lithium-rich positive electrode material, which comprises the following steps: 1) uniformly mixing lithium hydroxide and a Ni0. 6Co0. 15Mn0. 15 (OH) 1.8 precursor, sintering, and grinding to obtain a Li [Li0. 2Ni0. 6Co0. 15Mn0. 15] O2 positive electrode material; (2) Mo is subjected to atomic deposition on a molybdenum oxide substrate through the ALD technology, and a deposition material is obtained; and 3) adding the intermediate solution, the deposition material and the positive electrode material into a stirring kettle, performing homogenization under the protection of nitrogen, then performing replacement and washing with deionized water, then performing vacuum drying, and then performing sintering and grinding in a tubular furnace under the nitrogen atmosphere to obtain the lithium-rich positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of positive electrode materials, and more specifically, to a lithium-rich positive electrode material and a preparation method and application thereof. Background Art

[0002] Ternary layered structure of Li[Ni-Co-Mn]O 2 Lithium-ion battery positive electrode materials have the advantages of high discharge capacity, good safety performance and low toxicity, becoming a hot topic for technicians to study and are the development trend of lithium-ion battery positive electrode materials for high energy density hybrid vehicles.

[0003] Although Li[Ni-Co-Mn]O 2 The discharge capacity of lithium-ion battery cathode materials is very high, but the cycle performance is poor, especially the high charge cut-off voltage and high rate charge and discharge performance need to be further improved. In addition, in the application process, Li[Ni-Co-Mn]O 2 Ternary materials also have the following problems: 1. The mixing of cations in the lithium layer leads to a decrease in the initial charge and discharge efficiency; 2. The layered compounds of the material have poor thermodynamic stability after delithiation and are prone to oxygen loss and phase change; 3. In a wide range of discharge voltages, strong side reactions are likely to occur between the organic electrolyte and the electrode material, increasing the impedance of the battery during the charge and discharge process, thereby reducing the electrochemical performance of the material.

[0004] For Li[Ni-Co-Mn]O 2 To solve the current problems of ternary materials, a more effective method is to carry out surface coating modification, which currently mainly includes carbon coating and oxide coating. Carbon coating is to use carbon source to generate carbon through high-temperature cracking and evenly coat the surface of the material, which can reduce the charge transfer resistance of the positive electrode material during the charging and discharging process; oxide coating is to modify the surface of the positive electrode material with oxide, maintain the high initial capacity of the positive electrode active material itself, prevent the dissolution of metal ions in the electrolyte, and inhibit the occurrence of side reactions, thereby improving the capacity retention rate of the positive electrode material.

[0005] For the above coating modification method, Li[Ni-Co-Mn]O 2 The cycle performance of ternary materials has been improved to a certain extent, but there is still a lot of room for improvement in view of the growing demand for battery performance. Therefore, how to improve the coating modification method to further enhance the electrochemical performance of the positive electrode material is a hot issue that technicians need to solve urgently. Summary of the invention

[0006] In order to further improve the Li[Ni-Co-Mn]O 2 The electrochemical properties of ternary positive electrode materials. The present application provides a lithium-rich positive electrode material and a preparation method and application thereof.

[0007] In the first aspect, the present application provides a method for preparing a modified composite ternary positive electrode material, using the following technical solution: A method for preparing a lithium-rich positive electrode material comprises the following steps: 1) Prepare a mixed solution with nickel sulfate, cobalt sulfate and manganese sulfate, then add an appropriate amount of complexing agent and mix evenly to obtain a pre-liquid, then add the pre-liquid and precipitant into the reactor, and react under nitrogen protection to synthesize Ni 0.6 Co 0.15 Mn 0.15 (OH) 1.8 Precursor: Lithium hydroxide and Ni 0.6 Co 0.15 Mn 0.15 (OH) 1.8 The precursors are mixed evenly, sintered and ground to obtain Li[Li 0.2 Ni 0.6 Co 0.15 Mn 0.15 ]O 2 Cathode material; 2) Will WO 3 As the substrate, Mo(CO) 6 As molybdenum source, O 3 As an oxygen source, Mo is atomically deposited on a molybdenum oxide substrate by an ALD process to obtain a deposition material; polyethylene glycol, alkyl quaternary ammonium base, dimethyl sulfoxide and cellulose are uniformly mixed to obtain an intermediate solution; 3) Add the intermediate liquid, sediment and Li[Li 0.2 Ni 0.6 Co 0.15 Mn 0.15 ]O 2 The positive electrode material is homogenized under nitrogen protection, replaced and washed with deionized water, and then vacuum dried. It is then sintered in a tubular furnace under a nitrogen atmosphere and ground to obtain a lithium-rich positive electrode material.

[0008] Preferably, in step 1), the complexing agent includes hydroxyproline and sodium lactate.

[0009] Preferably, in step 1), lithium hydroxide and Ni 0.6 Co 0.15 Mn 0.15 (OH) 1.8 The molar ratio of the precursors is (1.25-1.3):1.

[0010] Preferably, in step 1), the sintering is first performed at a temperature of 450-550° C. for 5-6 hours, and then at a temperature of 900-980° C. for 10-15 hours.

[0011] Preferably, in step 2), the molar ratio of W to Mo in the deposited material is controlled within the range of 1:(0.7-0.85).

[0012] Preferably, in step 3), the deposited material accounts for Li[Li 0.2 Ni 0.6 Co 0.15 Mn 0.15 ]O 2 1.5-2.5wt% of the positive electrode material mass.

[0013] Preferably, in step 2), the molecular weight of the polyethylene glycol is 600-2000.

[0014] Preferably, in step 2), the alkyl quaternary ammonium base is one or more of tetramethylammonium hydroxide, tetrapropylammonium hydroxide and tetrabutylammonium hydroxide.

[0015] Preferably, in step 2), cellulose accounts for 0.03-0.05 wt% of the mass of the intermediate liquid.

[0016] In a second aspect, the present application provides a lithium-rich positive electrode material, which is prepared using the above-mentioned preparation method.

[0017] In a third aspect, the present application provides an application of a lithium-rich positive electrode material, wherein the lithium-rich positive electrode material is used in the preparation of a lithium-ion battery.

[0018] In summary, this application has the following beneficial effects: 1. This application adopts the co-deposition method to prepare the ternary positive electrode material, and adjusts the ratio of various elements and the lithium content. The positive electrode material prepared by sintering has a good layered structure and a low cation mixing degree. In addition, the excess lithium can replace other metal ions in the transition metal layer, making the material structure more stable. In addition, the ALD process is used on WO 3 Depositing and embedding Mo atoms on the substrate, introducing more oxygen vacancies, and utilizing the modification effect of W and Mo atoms can effectively inhibit the occurrence of electrolyte side reactions, reduce the impedance of the battery, greatly improve the rate performance of the positive electrode material, and improve the electrochemical performance of the material. Moreover, since there is a microscopic distance between the position of the deposited and embedded Mo atoms and the position of the original W atoms, this microscopic interatomic distance can produce a spatial separation synergy between the W and Mo atoms, thereby enhancing the oxygen vacancy effect, ensuring that a sufficient amount of lithium ions can return to the positive electrode material during the subsequent discharge process, further improving the electrochemical performance of the material.

[0019] 2. In this application, polyethylene glycol, alkyl quaternary ammonium base, dimethyl sulfoxide and cellulose are used to prepare an intermediate solution, and then the sediment material and Li[Li 0.2 Ni 0.6Co 0.15 Mn 0.15 ]O 2 The positive electrode material is added to the intermediate solution, and under the molecular embedding and intercalation of polyethylene glycol, the deposited material and Li[Li 0.2 Ni 0.6 Co 0.15 Mn 0.15 ]O 2 A doping system is formed between the positive electrode materials, and a small amount of cellulose is dissolved by the alkyl quaternary ammonium base, which can form a heterogeneous dissolution system in the intermediate solution, and then cooperate with the doping system. After subsequent replacement and sintering, the deposited material is 0.2 Ni 0.6 Co 0.15 Mn 0.15 ]O 2 A uniform coating layer is formed on the surface of the positive electrode material. On the other hand, after the high-temperature cracking and carbonization of trace cellulose, a trace amount of carbon doping coating will be formed in the ternary material, which can further reduce the charge transfer resistance of the positive electrode material during the charging and discharging process. In addition, the multiple modification effects of the sedimentary material and trace carbon can obtain a very good composite effect, thereby improving the electrochemical properties of the positive electrode material.

[0020] 3. The lithium-rich positive electrode material prepared by the preparation method of the present application has excellent rate performance and cycle performance, and can be used in lithium-ion batteries to improve the electrochemical performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a schematic diagram of the rate performance of the lithium-rich positive electrode material of Example 1 of the present application.

[0022] Figure 2 This is a schematic diagram of the rate performance of the lithium-rich positive electrode material of Example 2 of the present application.

[0023] Figure 3 This is a schematic diagram of the rate performance of the lithium-rich positive electrode material of Example 3 of the present application.

[0024] Figure 4 It is a schematic diagram of the rate performance of the lithium-rich positive electrode material of comparative example 1 of the present application.

[0025] Figure 5 It is a schematic diagram of the rate performance of the lithium-rich positive electrode material of Comparative Example 2 of the present application. DETAILED DESCRIPTION

[0026] The present application is further described in detail below with reference to the embodiments.

[0027] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.

[0028] Example 1 The method for preparing the lithium-rich positive electrode material of this embodiment comprises the following steps: 1) Nickel sulfate, cobalt sulfate and manganese sulfate are used to prepare a mixed solution with a concentration of 2 mol / L. Then, an appropriate amount of complexing agent is added and mixed evenly to obtain a pre-liquid. Then, a dual-channel peristaltic pump is used to add the pre-liquid and the precipitant into the reactor respectively. Ni is synthesized by reaction under nitrogen protection. 0.6 Co 0.15 Mn 0.15 (OH) 1.8 The precursor was maintained at a pH of about 10.5 during the entire reaction, with a stirring speed of 850 rpm and a reaction temperature of 50 °C. After the reaction was completed, it was aged for 12 h, then washed with deionized water, and centrifuged to obtain Ni 0.6 Co 0.15 Mn 0.15 (OH) 1.8 Precursor: Lithium hydroxide and Ni 0.6 Co 0.15 Mn 0.15 (OH) 1.8 The precursors were mixed evenly in a molar ratio of 1.25:1, sintered at 550°C for 5 h, then sintered at 900°C for 15 h, and ground and sieved to obtain Li[Li 0.2 Ni 0.6 Co 0.15 Mn 0.15 ]O 2 Cathode material; 2) WO with a purity of more than 99% 3 As a substrate, the surface was cleaned with hydrogen fluoride and deionized water before use to remove surface impurities; high-purity Mo(CO) 6 As molybdenum source, high purity O 3 The ALD process is used to atomically deposit Mo on a molybdenum oxide substrate as an oxygen source to obtain a deposited material. During the deposition process, the temperature of the substrate is controlled at 130-150°C, the heating temperature of the molybdenum source is 80°C, and the deposition power is set to 52W. The specific deposition process is: first, open the molybdenum source valve to introduce the molybdenum source for 5s, then open the oxygen source valve to introduce the oxygen source for 5s, then deposit and react for 60s, and finally open the vacuum valve to remove the residual substances; 20 mL of polyethylene glycol, 60 mL of alkyl quaternary ammonium base, 120 mL of dimethyl sulfoxide, and 0.06 g of cellulose were mixed uniformly to prepare an intermediate solution; 3) Add 500 mL of intermediate solution, 1.5 g of sediment and 100 g of Li[Li 0.2 Ni 0.6 Co 0.15 Mn 0.15 ]O 2The positive electrode material was homogenized under nitrogen protection, replaced and washed with deionized water, and then vacuum dried. It was then sintered at 500°C for 6 hours in a tubular furnace under a nitrogen atmosphere, and the lithium-rich positive electrode material was obtained after grinding.

[0029] The complexing agent is sodium lactate solution with a concentration of 2 mol / L. The precipitating agent is sodium hydroxide solution with a concentration of 4 mol / L. The molecular weight of polyethylene glycol is 600. The alkyl quaternary ammonium base is tetramethylammonium hydroxide with a mass concentration of 40%. The molar ratio of W to Mo in the sediment is controlled to be 1:(0.7-0.75).

[0030] The lithium-rich positive electrode material of this embodiment is prepared by the above-mentioned preparation method.

[0031] The application of the lithium-rich positive electrode material of this embodiment is to use the lithium-rich positive electrode material for preparing the positive electrode of a lithium-ion battery.

[0032] Example 2 The method for preparing the lithium-rich positive electrode material of this embodiment comprises the following steps: 1) Nickel sulfate, cobalt sulfate and manganese sulfate are used to prepare a mixed solution with a concentration of 2 mol / L. Then, an appropriate amount of complexing agent is added and mixed evenly to obtain a pre-liquid. Then, a dual-channel peristaltic pump is used to add the pre-liquid and the precipitant into the reactor respectively. Ni is synthesized by reaction under nitrogen protection. 0.6 Co 0.15 Mn 0.15 (OH) 1.8 The precursor was maintained at a pH of about 10.5 during the entire reaction, with a stirring speed of 850 rpm and a reaction temperature of 50 °C. After the reaction was completed, it was aged for 12 h, then washed with deionized water, and centrifuged to obtain Ni 0.6 Co 0.15 Mn 0.15 (OH) 1.8 Precursor: Lithium hydroxide and Ni 0.6 Co 0.15 Mn 0.15 (OH) 1.8 The precursors were mixed evenly in a molar ratio of 1.3:1, sintered at 450°C for 6 h, then sintered at 980°C for 10 h, and ground and sieved to obtain Li[Li 0.2 Ni 0.6 Co 0.15 Mn 0.15 ]O 2 Cathode material; 2) WO with a purity of more than 99% 3 As a substrate, the surface was cleaned with hydrogen fluoride and deionized water before use to remove surface impurities; high-purity Mo(CO) 6 As molybdenum source, high purity O3 The ALD process is used to atomically deposit Mo on a molybdenum oxide substrate as an oxygen source to obtain a deposited material. During the deposition process, the temperature of the substrate is controlled at 130-150°C, the heating temperature of the molybdenum source is 80°C, and the deposition power is set to 52W. The specific deposition process is: first, open the molybdenum source valve to introduce the molybdenum source for 5.5s, then open the oxygen source valve to introduce the oxygen source for 6s, then deposit and react for 70s, and finally open the vacuum valve to remove the residual substances; 20 mL of polyethylene glycol, 60 mL of alkyl quaternary ammonium base, 120 mL of dimethyl sulfoxide, and 0.1 g of cellulose were mixed uniformly to prepare an intermediate solution; 3) Add 500 mL of intermediate solution, 2.5 g of sediment and 100 g of Li[Li 0.2 Ni 0.6 Co 0.15 Mn 0.15 ]O 2 The positive electrode material was homogenized under nitrogen protection, replaced and washed with deionized water, and then vacuum dried. It was then sintered at 500°C for 6 hours in a tubular furnace under a nitrogen atmosphere, and the lithium-rich positive electrode material was obtained after grinding.

[0033] The complexing agent is a mixed solution of sodium lactate and hydroxyproline, the concentration of sodium lactate is 2 mol / L, and the concentration of hydroxyproline is 0.5 mol / L. The precipitant is a sodium hydroxide solution with a concentration of 4 mol / L. The molecular weight of polyethylene glycol is 2000. The alkyl quaternary ammonium base is tetrapropylammonium hydroxide with a mass concentration of 40%. The molar ratio of W to Mo in the sediment is controlled to be 1:(0.8-0.85).

[0034] The lithium-rich positive electrode material of this embodiment is prepared by the above-mentioned preparation method.

[0035] The application of the lithium-rich positive electrode material of this embodiment is to use the lithium-rich positive electrode material for preparing the positive electrode of a lithium-ion battery.

[0036] Example 3 The method for preparing the lithium-rich positive electrode material of this embodiment comprises the following steps: 1) Nickel sulfate, cobalt sulfate and manganese sulfate are used to prepare a mixed solution with a concentration of 2 mol / L. Then, an appropriate amount of complexing agent is added and mixed evenly to obtain a pre-liquid. Then, a dual-channel peristaltic pump is used to add the pre-liquid and the precipitant into the reactor respectively. Ni is synthesized by reaction under nitrogen protection. 0.6 Co 0.15 Mn 0.15 (OH) 1.8 The precursor was maintained at a pH of about 10.5 during the entire reaction, with a stirring speed of 850 rpm and a reaction temperature of 50 °C. After the reaction was completed, it was aged for 12 h, then washed with deionized water, and centrifuged to obtain Ni0.6 Co 0.15 Mn 0.15 (OH) 1.8 Precursor: Lithium hydroxide and Ni 0.6 Co 0.15 Mn 0.15 (OH) 1.8 The precursors were mixed evenly in a molar ratio of 1.265:1, sintered at 500°C for 5 h, then sintered at 950°C for 12 h, and ground and sieved to obtain Li[Li 0.2 Ni 0.6 Co 0.15 Mn 0.15 ]O 2 Cathode material; 2) WO with a purity of more than 99% 3 As a substrate, the surface was cleaned with hydrogen fluoride and deionized water before use to remove surface impurities; high-purity Mo(CO) 6 As molybdenum source, high purity O 3 The ALD process is used to atomically deposit Mo on a molybdenum oxide substrate as an oxygen source to obtain a deposited material. During the deposition process, the temperature of the substrate is controlled at 130-150°C, the heating temperature of the molybdenum source is 80°C, and the deposition power is set to 52W. The specific deposition process is: first, open the molybdenum source valve to introduce the molybdenum source for 5.5s, then open the oxygen source valve to introduce the oxygen source for 5s, then deposit and react for 65s, and finally open the vacuum valve to remove the residual substances; 20 mL of polyethylene glycol, 60 mL of alkyl quaternary ammonium base, 120 mL of dimethyl sulfoxide, and 0.08 g of cellulose were mixed uniformly to prepare an intermediate solution; 3) Add 500 mL of intermediate solution, 2 g of sediment and 100 g of Li[Li 0.2 Ni 0.6 Co 0.15 Mn 0.15 ]O 2 The positive electrode material was homogenized under nitrogen protection, replaced and washed with deionized water, and then vacuum dried. It was then sintered at 500°C for 6 hours in a tubular furnace under a nitrogen atmosphere, and the lithium-rich positive electrode material was obtained after grinding.

[0037] The complexing agent is a mixed solution of sodium lactate and hydroxyproline, the concentration of sodium lactate is 2 mol / L, and the concentration of hydroxyproline is 0.5 mol / L. The precipitant is a sodium hydroxide solution with a concentration of 4 mol / L. The molecular weight of polyethylene glycol is 800. The alkyl quaternary ammonium base is tetrabutylammonium hydroxide with a mass concentration of 40%. The molar ratio of W to Mo in the sediment is controlled to be 1:(0.75-0.82).

[0038] The lithium-rich positive electrode material of this embodiment is prepared by the above-mentioned preparation method.

[0039] The application of the lithium-rich positive electrode material of this embodiment is to use the lithium-rich positive electrode material for preparing the positive electrode of a lithium-ion battery.

[0040] Comparative Example 1 The preparation method of the lithium-rich positive electrode material of this comparative example comprises the following steps: 1) Nickel sulfate, cobalt sulfate and manganese sulfate are used to prepare a mixed solution with a concentration of 2 mol / L. Then, an appropriate amount of complexing agent is added and mixed evenly to obtain a pre-liquid. Then, a dual-channel peristaltic pump is used to add the pre-liquid and the precipitant into the reactor respectively. Ni is synthesized by reaction under nitrogen protection. 0.6 Co 0.15 Mn 0.15 (OH) 1.8 The precursor was maintained at a pH of about 10.5 during the entire reaction, with a stirring speed of 850 rpm and a reaction temperature of 50 °C. After the reaction was completed, it was aged for 12 h, then washed with deionized water, and centrifuged to obtain Ni 0.6 Co 0.15 Mn 0.15 (OH) 1.8 Precursor: Lithium hydroxide and Ni 0.6 Co 0.15 Mn 0.15 (OH) 1.8 The precursors were mixed evenly in a molar ratio of 1.25:1, sintered at 550°C for 5 h, then sintered at 900°C for 15 h, and ground and sieved to obtain Li[Li 0.2 Ni 0.6 Co 0.15 Mn 0.15 ]O 2 Cathode material; 2) Add 500 mL of deionized water, 1.5 g of aluminum hydroxide and 100 g of Li[Li 0.2 Ni 0.6 Co 0.15 Mn 0.15 ]O 2 The positive electrode material is prepared by adding ammonia water to control the pH value to about 9. After the reaction under nitrogen protection, the excess water is evaporated, and then the material is vacuum dried. Subsequently, the material is sintered at 500°C for 6 hours in a tubular furnace under a nitrogen atmosphere, and the lithium-rich positive electrode material is obtained after grinding.

[0041] The complexing agent is sodium lactate solution with a concentration of 2 mol / L, and the precipitating agent is sodium hydroxide solution with a concentration of 4 mol / L.

[0042] The lithium-rich positive electrode material of this comparative example is prepared by the above-mentioned preparation method.

[0043] The application of the lithium-rich positive electrode material of this comparative example is to use the lithium-rich positive electrode material for the preparation of the positive electrode of a lithium-ion battery.

[0044] Comparative Example 2 The preparation method of the lithium-rich positive electrode material of this comparative example comprises the following steps: 1) Nickel sulfate, cobalt sulfate and manganese sulfate are used to prepare a mixed solution with a concentration of 2 mol / L. Then, an appropriate amount of complexing agent is added and mixed evenly to obtain a pre-liquid. Then, a dual-channel peristaltic pump is used to add the pre-liquid and the precipitant into the reactor respectively. Ni is synthesized by reaction under nitrogen protection. 0.6 Co 0.15 Mn 0.15 (OH) 1.8 The precursor was maintained at a pH of about 10.5 during the entire reaction, with a stirring speed of 850 rpm and a reaction temperature of 50 °C. After the reaction was completed, it was aged for 12 h, then washed with deionized water, and centrifuged to obtain Ni 0.6 Co 0.15 Mn 0.15 (OH) 1.8 Precursor: Lithium hydroxide and Ni 0.6 Co 0.15 Mn 0.15 (OH) 1.8 The precursors were mixed evenly in a molar ratio of 1.25:1, sintered at 550°C for 5 h, then sintered at 900°C for 15 h, and ground and sieved to obtain Li[Li 0.2 Ni 0.6 Co 0.15 Mn 0.15 ]O 2 Cathode material; 2) WO with a purity of more than 99% 3 As a substrate, the surface was cleaned with hydrogen fluoride and deionized water before use to remove surface impurities; high-purity Mo(CO) 6 As molybdenum source, high purity O 3 The ALD process is used to atomically deposit Mo on a molybdenum oxide substrate as an oxygen source to obtain a deposited material. During the deposition process, the temperature of the substrate is controlled at 130-150°C, the heating temperature of the molybdenum source is 80°C, and the deposition power is set to 52W. The specific deposition process is: first, open the molybdenum source valve to introduce the molybdenum source for 5s, then open the oxygen source valve to introduce the oxygen source for 5s, then deposit and react for 60s, and finally open the vacuum valve to remove the residual substances; 3) Add 500 mL of deionized water, 1.5 g of sediment and 100 g of Li[Li 0.2 Ni 0.6 Co 0.15 Mn 0.15 ]O 2The positive electrode material was homogenized under nitrogen protection and then vacuum dried, then sintered at 500°C for 6h in a tubular furnace under a nitrogen atmosphere, and then ground to obtain a lithium-rich positive electrode material.

[0045] The complexing agent is a sodium lactate solution with a concentration of 2 mol / L. The precipitating agent is a sodium hydroxide solution with a concentration of 4 mol / L. The molar ratio of W to Mo in the sediment is controlled to be 1:(0.7-0.75).

[0046] The lithium-rich positive electrode material of this comparative example is prepared by the above-mentioned preparation method.

[0047] The application of the lithium-rich positive electrode material of this comparative example is to use the lithium-rich positive electrode material for the preparation of the positive electrode of a lithium-ion battery.

[0048] Performance testing Battery assembly: The lithium-rich positive electrode materials, acetylene carbon black, and PVDF of Examples 1-3 and Comparative Examples 1-2 were mixed uniformly in a mass ratio of 8:1:1, and then an appropriate amount of N-methylpyrrolidone was added and stirred to form a slurry, which was then coated on an aluminum foil and vacuum dried and cut into φ12mm positive electrode sample pieces. Then, a lithium sheet was used as the negative electrode, and a 1 mol / L lithium hexafluorophosphate mixed solution of ethylene carbonate, methyl ethyl carbonate, and dimethyl carbonate was used as the electrolyte. The button cells were assembled in a glove box and placed on an electrochemical tester for electrochemical performance testing. The test results are shown in Tables 1 and Figure 1-5 shown.

[0049] Table 1 Electrochemical performance test results of the first charge and discharge of the lithium-rich positive electrode materials of Examples 1-3 and Comparative Examples 1-2 at a current density of 20 mA / g Analyze Examples 1-3 and Comparative Examples 1-2 and combine Table 1 and Figure 1-5 It can be seen that the lithium-rich positive electrode material of the present application has a higher charge and discharge specific capacity and a very good rate performance. Compared with traditional metal oxide coating materials, it can further improve the electrochemical performance of the battery.

[0050] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A method for preparing a lithium-rich positive electrode material, characterized in that: The steps include: 1) Prepare a mixed solution with nickel sulfate, cobalt sulfate and manganese sulfate, then add an appropriate amount of complexing agent and mix evenly to obtain a pre-liquid, then add the pre-liquid and precipitant into the reactor, and react under nitrogen protection to synthesize Ni 0.6 Co 0.15 Mn 0.15 (OH) 1.8 Precursor: Lithium hydroxide and Ni 0.6 Co 0.15 Mn 0.15 (OH) 1.8 The precursors are mixed evenly, sintered and ground to obtain Li[Li 0.2 Ni 0.6 Co 0.15 Mn 0.15 ]O2 positive electrode material; 2) Using WO3 as a substrate, Mo(CO)6 as a molybdenum source, and O3 as an oxygen source, an ALD process is used to atomically deposit Mo on the molybdenum oxide substrate to obtain a deposited material; polyethylene glycol, alkyl quaternary ammonium base, dimethyl sulfoxide, and cellulose are uniformly mixed to obtain an intermediate solution; 3) Add the intermediate liquid, sediment and Li[Li 0.2 Ni 0.6 Co 0.15 Mn 0.15 ]O2 positive electrode material is homogenized under nitrogen protection, replaced and washed with deionized water, and then vacuum dried. It is then sintered in a tubular furnace under a nitrogen atmosphere and ground to obtain a lithium-rich positive electrode material.

2. The method for preparing a lithium-rich positive electrode material according to claim 1, characterized in that: In the step 1), the complexing agent includes hydroxyproline and sodium lactate.

3. The method for preparing a lithium-rich positive electrode material according to claim 1, characterized in that: In the step 1), lithium hydroxide and Ni 0.6 Co 0.15 Mn 0.15 (OH) 1.8 The molar ratio of the precursors is (1.25-1.3):

1.

4. The method for preparing a lithium-rich positive electrode material according to claim 1, characterized in that: In the step 1), the sintering is first performed at a temperature of 450-550° C. for 5-6 hours, and then at a temperature of 900-980° C. for 10-15 hours.

5. The method for preparing a lithium-rich positive electrode material according to claim 1, characterized in that: In the step 2), the molar ratio of W to Mo in the deposited material is controlled to be in the range of 1:(0.7-0.85).

6. The method for preparing a lithium-rich positive electrode material according to claim 1, characterized in that: In step 3), the deposited material accounts for Li[Li 0.2 Ni 0.6 Co 0.15 Mn 0.15 ]1.5-2.5wt% of the mass of O2 positive electrode material.

7. The method for preparing a lithium-rich positive electrode material according to claim 1, characterized in that: In the step 2), the molecular weight of the polyethylene glycol is 600-2000.

8. The method for preparing a lithium-rich positive electrode material according to claim 1, characterized in that: In the step 2), the alkyl quaternary ammonium base is one or more of tetramethylammonium hydroxide, tetrapropylammonium hydroxide and tetrabutylammonium hydroxide.

9. A lithium-rich positive electrode material, characterized in that: The method is prepared by any one of claims 1 to 8.

10. An application of a lithium-rich positive electrode material, characterized in that: The lithium-rich positive electrode material prepared by the preparation method according to any one of claims 1 to 8 or the lithium-rich positive electrode material according to claim 9 is used for preparing a lithium-ion battery.

Citation Information

Patent Citations

  • Method for synthesizing cathodic material of high-capacity lithium ion battery

    CN102244237A

  • Improved lithium-rich manganese-based lithium-ion battery cathode material and preparation method and application

    CN105244494A

  • Controllable pH value -based preparation method for lithium ion battery positive electrode material

    CN106935847A

  • High-energy-density ternary positive electrode material as well as preparation method and application thereof

    CN114426313A

  • Bulk-phase-doped ternary positive electrode material coated with lithium ion conductor on surface and preparation method and application of bulk-phase-doped ternary positive electrode material

    CN115377385A